Burden of Cardiovascular Disease among Multi-Racial and Ethnic Populations in the United States: an Update from the National Health Interview Surveys - Liu, Longjian; Núṅez, Ana E.; An, Yuan; Liu, Hui; Chen, Ming; Ma, Jixiang; Chou, Edgar Y.; Chen, Zhengming; Eisen, Howard J. (Frontiers in Cardiovascular Medicine, 2014)
Purpose: The study aimed to provide new evidence of health disparities in cardiovascular disease (CVD) and diabetes mellitus (DM), and to examine their associations with lifestyle-related risk factors across the U.S. multi-racial and ethnic groups. Methods: The analysis included a randomized population sample of 68,321 subjects aged ≥18 years old who participated in the U.S. 2012 and 2013 National Health Interview Surveys. Hypertension, coronary heart disease (CHD), stroke, and DM were classified according to participants’ self-report of physician diagnosis. Assessments of risk factors were measured using standard survey instruments. Associations of risk factors with hypertension, CHD, stroke, and DM were analyzed using univariable and multivariable analysis methods. Results: Non-Hispanic (NH)-Blacks had significantly higher odds of hypertension, while Hispanics had significantly lower odds of hypertension, and NH-Asians and Hispanics had significantly lower odds of stroke than NH-Whites (p < 0.001). All minority groups, NH-Blacks, NH-Asians, and Hispanics had significantly higher odds of DM, but they had significantly lower odds of CHD than NH-Whites (p < 0.001). Increased body weight, cigarette smoking, and physical inactivity were significantly associated with increased odds of hypertension, CHD, stroke, and DM (p < 0.001). However, the strengths of associations between lifestyle-related factors and the study outcomes were different across racial and ethnic groups. NH-Asians with BMI ≥30 kg/m2 had the highest odds ratios (OR, 95% CI) for hypertension (5.37, 4.01–7.18), CHD (2.93, 1.90–4.52), and stroke (2.23, 1.08–4.61), and had the second highest odd ratios for DM (3.78, 2.68–5.35) than NH-Whites, NH-Blacks, and Hispanics. Conclusion: CVD and DM disproportionately affect the U.S. multi-racial and ethnic population. Although lifestyle-related risk factors are significantly associated with increased odds of CVD and DM, the magnitudes of these associations are different by race and ethnicity.